PENERAPAN E-COMMERCE DALAM PENGUATAN DAYA SAING USAHA MELALUI STARTUP (STUDI KASUS PERUSAHAAN GPS MEDAN) - Utia Elja Rizki; Marliyah Marliyah; Nurbaiti Nurbaiti (Universitas Islam Negeri Sumatera Utara, 2021)
The rapid advancement of technology in Indonesia creates opportunities for the business world to be supported and supported by government programs so that many business actors take advantage of e-commerce to continue to be able to compete in today's technological developments. However, this is inversely proportional to the public's interest in implementing e-commerce in their business. This study aims to see the application of e-commerce through startups that can strengthen the business competitiveness of GPS Medan, then see what the motives of GPS Medan players in implementing e-commerce through startups and see how the impact of the application of e-commerce in strengthening business competitiveness. Terrain GPS via startup. The method used in this research is a comparative method that is descriptive qualitative with in-depth interviews which is supported by a documentation study of sthe company and consumers of the Medan GPS company. The results showed that the application of e-commerce through the startup GPS Medan was able to increase the market, increase the ability to innovate and facilitate consumer transactions so as to increase the business competitiveness of the GPS Medan company. In addition, the motive that encourages business actors to implement e-commerce through startups is that businesses will be more trusted and increase credibility, startup businesses also do not need a strategic office, increase market news, and can build strong branding and identity, and have a positive impact in increasing number of consumers, sales, income, creating jobs, and the opportunity to add new business services as a result of understanding technology.